A small-scale, portable method for extracting microplastics from marine sediments. (November 2017) - Coppock, Rachel L.; Cole, Matthew; Lindeque, Penelope K.; Queirós, Ana M.; Galloway, Tamara S.
Abstract: Microplastics (plastic particles, 0.1 μm–5 mm in size) are widespread marine pollutants, accumulating in benthic sediments and shorelines the world over. To gain a clearer understanding of microplastic availability to marine life, and the risks they pose to the health of benthic communities, ecological processes and food security, it is important to obtain accurate measures of microplastic abundance in marine sediments. To date, methods for extracting microplastics from marine sediments have been disadvantaged by complexity, expense, low extraction efficiencies and incompatibility with very fine sediments. Here we present a new, portable method to separate microplastics from sediments of differing types, using the principle of density floatation. The Sediment-Microplastic Isolation (SMI) unit is a custom-built apparatus which consistently extracted microplastics from sediments in a single step, with a mean efficiency of 95.8% (±SE 1.6%; min 70%, max 100%). Zinc chloride, at a density of 1.5 g cm −3, was deemed an effective and relatively inexpensive floatation media, allowing fine sediment to settle whilst simultaneously enabling floatation of dense polymers. The method was validated by artificially spiking sediment with low and high density microplastics, and its environmental relevance was further tested by extracting plastics present in natural sediment samples from sites ranging in sediment type; fine silt/clay (mean size 10.25 ± SD 3.02 μm) to coarse sand (mean size 149.3 ± SD 49.9 μm). The method presented here is cheap, reproducible and is easily portable, lending itself for use in the laboratory and in the field, eg. on board research vessels. By employing this method, accurate estimates of microplastic type, distribution and abundance in natural sediments can be achieved, with the potential to further our understanding of the availability of microplastics to benthic organisms. Graphical abstract: Highlights: Cheap, effective method for microplastic extraction from sediments. High, reproducible recovery rates - 95.8%. Comparison of three commonly used floatation media. Zinc chloride (1.5 g cm −3 ) deemed an effective floatation medium. Method applied to environmental samples across a range of sediment types. Abstract : We present a simple, portable method to extract microplastics from natural sediments of different grain size using zinc chloride density floatation, yielding accurate and reproducible results.